2018
DOI: 10.1111/papr.12732
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in Breast Cancer Survivors: Nociceptive, Neuropathic, or Central Sensitization Pain?

Abstract: Introduction The differentiation between acute and chronic pain can be insufficient for appropriate pain management. The aim of this study was to evaluate the prevalence of the predominant pain type (nociceptive, neuropathic, or central sensitization [CS] pain) in breast cancer survivors (BCS) with chronic pain. The secondary aims were to examine (1) differences in health‐related quality of life (HRQoL) between the different pain groups; and (2) the associations between patient‐, disease‐, and treatment‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 71 publications
5
65
0
2
Order By: Relevance
“…In 18 (20.9%) patients with CPBS, the median NRS values recorded during movement were greater than ve, therefore re ecting moderate to severe chronic pain. These results are in line with those reported in the literature (Andersen and Kehlet 2013;Leysen et al 2018;Peuckmann et al 2009). Finally, according to the BPI questionnaire, CPBS had a profound impact on sleep quality, mood and perception of happiness.…”
Section: Discussionsupporting
confidence: 93%
“…In 18 (20.9%) patients with CPBS, the median NRS values recorded during movement were greater than ve, therefore re ecting moderate to severe chronic pain. These results are in line with those reported in the literature (Andersen and Kehlet 2013;Leysen et al 2018;Peuckmann et al 2009). Finally, according to the BPI questionnaire, CPBS had a profound impact on sleep quality, mood and perception of happiness.…”
Section: Discussionsupporting
confidence: 93%
“…There are several reasons why the follow-up patients scored high on pain intensity or was not prescribed pain medications in accordance to their pain intensity and wanted more focus on pain. Studies have demonstrated that cancer survivors do have a significant symptom burden (33,34). In a busy clinic where both follow-up patients, patients receiving cancer treatment, and patients in palliative care setting are handled, the follow-up patients might not be given enough attention for their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They may arise shortly after surgery and/or adjuvant treatment and can remain as a source of physical and psychological distress for several years [11]. Consequently, shoulder morbidity and pain after breast cancer treatment have received considerable attention in the literature with several recent reviews examining the extent of these issues [6], [12][13][14].…”
Section: Introductionmentioning
confidence: 99%